Nonlinear p-ary sequences - Ling, San (2013)
Low correlation p-ary sequences with p an odd prime are constructed. They are obtained as Gray images of codewords of a subcode of the generalized Kerdock codes over the ring ℤ p 2. They can be shown to be nonlinear in some precise sense.